2017
DOI: 10.1128/jvi.00333-17
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacies of Formaldehyde-Inactivated Whole-Virus Vaccine and Antivirals in a Murine Model of Coxsackievirus A10 Infection

Abstract: Coxsackievirus A10 (CVA10) is one of the major pathogens associated with hand, foot, and mouth disease (HFMD). CVA10 infection can cause herpangina and viral pneumonia, which can be complicated by severe neurological sequelae. The morbidity and mortality of CVA10-associated HFMD have been increasing in recent years, particularly in the pan-Pacific region. There are limited studies, however, on the pathogenesis and immunology of CVA10-associated HFMD infections, and few antiviral drugs or vaccines have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 39 publications
(34 reference statements)
1
26
5
Order By: Relevance
“…Clinical studies have shown that the high expressions of several cytokines, such as IL-6, TNF-α, and IL-10, are closely correlated with clinical manifestations and complications associated with CV-B4 infection ( Alidjinou et al, 2013 ; Gu et al, 2009 ). Our data showed that after neonatal mice were inoculated with CV-B4, there was a gradual increase in the level of IL-6 in serum, different from that observed in enterovirus species A virus infection (CV-A6 and CV-A10) in ICR neonatal mice ( Zhang et al, 2017a , b ). Our previous studies on CV-A6 and CV-A10 mouse models of infection also showed high expression levels of IL-6 throughout all stages of infection ( Zhang et al, 2017a , b ).…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Clinical studies have shown that the high expressions of several cytokines, such as IL-6, TNF-α, and IL-10, are closely correlated with clinical manifestations and complications associated with CV-B4 infection ( Alidjinou et al, 2013 ; Gu et al, 2009 ). Our data showed that after neonatal mice were inoculated with CV-B4, there was a gradual increase in the level of IL-6 in serum, different from that observed in enterovirus species A virus infection (CV-A6 and CV-A10) in ICR neonatal mice ( Zhang et al, 2017a , b ). Our previous studies on CV-A6 and CV-A10 mouse models of infection also showed high expression levels of IL-6 throughout all stages of infection ( Zhang et al, 2017a , b ).…”
Section: Discussioncontrasting
confidence: 80%
“…Our data showed that after neonatal mice were inoculated with CV-B4, there was a gradual increase in the level of IL-6 in serum, different from that observed in enterovirus species A virus infection (CV-A6 and CV-A10) in ICR neonatal mice ( Zhang et al, 2017a , b ). Our previous studies on CV-A6 and CV-A10 mouse models of infection also showed high expression levels of IL-6 throughout all stages of infection ( Zhang et al, 2017a , b ). Therefore, we speculate that the differences in pathogenicity between CV-A and CV-B enteroviral species in the same neonatal ICR murine model may be attributable to differences in skeletal muscle tropisms and proinflammatory cytokine expression levels, such as that of IL-6, in peripheral blood.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations